MASYARAKAT INDONESIA DALAM BINGKAI PERUBAHAN DIALEKTIS - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2007)
The main concern of this writing will be addressed to social and political changes after the New Order era had lost control a power This era was may be called as a symbolic power of the last absolutely monarchy in Indonesia, even though this country had claimed that Indonesian is a republic democratic state and as an independent nation since 1945. A common thesis demonstrates that democratic state will establish after an authoritarian slate is not gain in power. It is an ideological claimed instead of existing reality In spite of promot¬ing democratic principles, which is sponsored by middle class socieix social and political changes are still poor to adopt democratic principles within a social life. The current situ¬ation in Indonesia has colored the state that can not ensure the certainly life of its people. The uncertainty life has been taken place in every corner stone of social, economic, political and low performance, where social and political changes provide a space of anarchy The dialectical thesis of an authoritarian state in Indonesia, the state performance in the Reforma¬tion order after the previous one had gone. does not result democracy based on the ethical conduct to follow regulation and constitution that being ensured by low enforcement, but this change has appeared life style of anarchy. Does the democratic state establish after becom¬ing absolutely anarchy or it does not necessarly remain absolutely anarchy happened? This is a significant challenge of Indonesian society to struggle for ascertaining an atmosphere of democratic principles. Kara K unci : Otoriter berantitesis anarkhi, menuju sintesis demokrasi